The effect of whole-body electromyostimulation on visceral adipose tissue volume in overweight-to-obese adults with knee osteoarthritis: A randomized controlled study - Burkhardt, Benazir; Chaudry, Oliver; Kast, Stephanie; von Stengel, Simon; Kohl, Matthias; Roemer, Frank W.; Engelke, Klaus; Uder, Michael; Kemmler, Wolfgang (Frontiers in Physiology, 2025)
IntroductionPhysical exercise favorably affects visceral adipose tissue (VAT), which is a risk factor for cardiometabolic diseases. However, many people are unable or unwilling to conduct frequent and intensive exercise programs that have favorable effects on VAT. The present study aimed to determine the effect of time-efficient and joint-friendly whole-body electromyostimulation (WB-EMS) technology on VAT volume in overweight-to-obese adults with osteoarthritis of the knee.MethodsIn total, 46 women and 26 men (58.4 ± 7.0 years; BMI: 30.2 ± 4.2 kg/m2) with femuro-tibial knee osteoarthritis were randomly allocated to WB-EMS (n = 36) with 1.5 × 20 min/week for 29 weeks or a usual care control group (CG: n = 36) with six sessions of physiotherapy. Magnetic resonance imaging (MRI) using a non-contrast enhanced two-point Dixon gradient echo volumetric interpolated breath-hold examination determined the VAT from mid L2 to mid L3.ResultsIn summary, VAT volume increased non-significantly in the CG (p = 0.246) and decreased non-significantly in the WB-EMS group (p = 0.143). We failed to determine significant WB-EMS-induced effects, i.e., group differences for absolute changes in the VAT volume (p = 0.090). However, we observed gender differences with significantly higher effects in men than in women (p = 0.032).DiscussionWe conclude that low volume, non-superimposed WB-EMS is not a perfect tool for decreasing VAT, particularly in overweight-to-obese women.